Functional Cftr in crypt epithelium of organotypic enteroid cultures from murine small intestine - Liu, Jinghua (American Physiological Society, 2012)
Physiological studies of intact crypt epithelium have been limited by problems of accessibility in vivo and dedifferentiation in standard primary culture. Investigations of murine intestinal stem cells have recently yielded a primary intestinal culture in three-dimensional gel suspension that recapitulates crypt structure and epithelial differentiation (Sato T, Vries RG, Snippert HJ, van de Wetering M, Barker N, Stange DE, Van Es JH, Abo A, Kujala P, Peters PJ, Clevers H. Nature 459: 262–265, 2009). We investigated the utility of murine intestinal crypt cultures (termed “enteroids”) for physiological studies of crypt epithelium by focusing on the transport activity of the cystic fibrosis transmembrane conductance regulator Cftr. Enteroids had multiple crypts with well-differentiated goblet and Paneth cells that degranulated on exposure to the muscarinic agonist carbachol. Modified growth medium provided a crypt proliferation rate, as measured by 5-ethynyl-2′-deoxyuridine labeling, which was similar to proliferation in vivo. Immunoblots demonstrated equivalent Cftr expression in comparisons of freshly isolated crypts with primary and passage 1 enteroids. Apparent enteroid differences in mRNA expression of other transporters were primarily associated with villous epithelial contamination of freshly isolated crypts. Microelectrode analysis revealed cAMP-stimulated membrane depolarization in enteroid epithelium from wild-type (WT) but not Cftr knockout (KO) mice. Morphological and microfluorimetric studies, respectively, demonstrated Cftr-dependent cell shrinkage and lower intracellular pH in WT enteroid epithelium in contrast to Cftr KO epithelium or WT epithelium treated with Cftr inhibitor 172. We conclude that crypt epithelium of murine enteroids exhibit Cftr expression and activity that recapitulates crypt epithelium in vivo. Enteroids provide a primary culture model that is suitable for physiological studies of regenerating crypt epithelium.